Career choices of Nigerian youths entering public-funded universities (2014)
Choosing a career is a very challenging process especially among youths. Although career choices and career dynamics are given considerable research attention in the developed countries, these subjects do not attract sustained attention in developing countries. This study tried to fill this research gap and also rekindle desired attention in this research area. The study analyzed Nigeria’s publicly available Unified Tertiary Matriculation Examinations (UTME) s statistics for 2003 and 2007. The focus was on public universities. Results showed that for 2003 and 2007, there were: significant variability in the choices of courses by male and female university admission applicants (more males than females chose science, engineering, and other "hard" courses) ; and significant variability in admission trends for Northern and Southern Nigerian regions (more southern than northern applicants sought to enter the university and chose science, engineering, and other "hard" courses). It was noted that these findings have serious implications for Nigeria’s future educational planning and outcomes. Further suggestions were proposed.